2008
DOI: 10.1007/s12192-008-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C signaling during T cell activation induces the endoplasmic reticulum stress response

Abstract: T cell receptor (TCR) ligation (signal one) in the presence of co-stimulation (signal two) results in downstream signals that increase protein production enabling naïve T cells to fully activate and gain effector function. Enhanced production of proteins by a cell requires an increase in endoplasmic reticulum (ER) chaperone expression, which is accomplished through activation of a cellular mechanism known as the ER stress response. The ER stress response is initiated during the cascade of events that occur for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Our results show that pre-treatment with wogonin significantly reduces the intracellular DAG levels and attenuates PKC phosphorylation (Figure 7). Because activated PKCs may contribute to altered cellular functions such as regulating signaling function of the ER [54,55] and enhancing ROS production [51] , our data suggest that the DAG/PKC pathway mediates palmitate-induced apoptosis and overgenerated ROS production in VSMCs, and that wogonin ameliorates palmitate-induced ER stress by inhibiting the DAG-PKC pathway.…”
Section: Discussionmentioning
confidence: 83%
“…Our results show that pre-treatment with wogonin significantly reduces the intracellular DAG levels and attenuates PKC phosphorylation (Figure 7). Because activated PKCs may contribute to altered cellular functions such as regulating signaling function of the ER [54,55] and enhancing ROS production [51] , our data suggest that the DAG/PKC pathway mediates palmitate-induced apoptosis and overgenerated ROS production in VSMCs, and that wogonin ameliorates palmitate-induced ER stress by inhibiting the DAG-PKC pathway.…”
Section: Discussionmentioning
confidence: 83%
“…This hypothesis was supported by the finding that Ca 2+ chelators abrogated TCR-mediated Grp78 expression. In contrast, Pino et al (47) argued that the protein kinase C-signaling pathway controls TCR-mediated Grp78 expression and additionally affects IL-2 expression. Consistently, we demonstrated that IL-2 expression and T cell proliferation are controlled by Grp78.…”
Section: Discussionmentioning
confidence: 94%
“…Two recent reports attempted to identify the signaling pathways triggering Grp78 expression after TCR activation (46,47). Takano et al (46) reported that this process might be regulated by the calcineurin-NFAT pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations